Analgesia after tonsillectomy with controlled intravenous morphine — overdue or exaggerated? - Magdalena Gostian; Johannes Loeser; Tanya Bentley; Philipp Wolber; David Schwarz; Matthias Balk; Antoniu-Oreste Gostian (Brazilian Journal of Otorhinolaryngology, 2023)
Objective: To assess the value of a morphine Patient Controlled Intravenous Analgesia (PCIA) after Tonsillectomies (TE). Methods: 30 adult patients were treated with oral analgesics (protocol group) and compared to 30 patients treated with a morphine PCIA for the first 3 Postoperative Days (PODs) after TE. Average and maximum pain severities (Numeric Rating Scale – NRS: 0–10) on PODs 1–3, analgesic score, quality of life, patient satisfaction and side effects were defined as outcome measures. Results: Average pain severities of the protocol and the PCIA group were of similar magnitude (NRS) (POD1: 4.48 vs. 4.71 [p = 0.68], POD2: 4.75 vs. 4.22 [p = 0.32] and POD3: 4.44 vs. 4.25 [p = 0.71]). Maximum pain intensities on POD1 (p = 0.92), POD2 (p = 0.51) and POD3 (p = 0.36) were also comparable between both groups. Patients with a PCIA consumed significantly more opioids (p = 0.001) without significant more side-effects. Conclusion: The PCIA did not provide a superior pain control compared to oral analgesics. In view of the considerable effort and the high opioid consumption, it cannot be recommended as a standardized application for pain control after TE.